Alteration of Extracellular Superoxide Dismutase in Idiopathic Pulmonary Arterial Hypertension - Zhang, Rui; Wang, Lan; Zhao, Qin-Hua; Jiang, Rong; Gong, Su-Gang; Jiang, Xin; Xu, Xi-Qi; He, Yang-Yang; Li, Yuan; Jing, Zhi-Cheng (Frontiers in Medicine, 2020)
Background: Superoxide dismutases (SODs) are an important family of antioxidant enzymes that modulate reactive oxidative species levels. It is largely unknown which SOD isoform(s) change in vivo in idiopathic pulmonary arterial hypertension (IPAH) patients. Methods: A total 133 consecutive adult IPAH patients who underwent bone morphogenetic protein receptor type 2 (BMPR2) genetic counseling were enrolled in this prospective study. Three subtypes of SODs [Copper-Zinc (Cu/Zn-SOD), Manganese (Mn-SOD) and extracellular SOD (Ec-SOD)] plasma activities were examined. Results: The activities of SODs were significantly lower in IPAH patients than in healthy subjects. However, only Ec-SOD activity with BMPR2 mutation patients were significantly decreased compared to those without mutation. Reduced Ec-SOD activity was markedly associated with mean pulmonary arterial pressure, pulmonary vascular resistance (PVR) and 6-minute walking distance (6MWD). Reduction of Mn-SOD activity was only associated with 6MWD, there was not association between Cu/Zn-SOD and hemodynamics. Patients with a lower Ec-SOD level had a worse survival compared to those with higher baseline. The reduced Ec-SOD activity and raised PVR remained an increased mortality risk. Conclusions: Ec-SOD was correlated with BMPR2 mutation, hemodynamic dysfunction and poor outcomes. Circulating Ec-SOD could be potentially vital antioxidant enzymes in pathogenesis of IPAH.